COOPERATION BETWEEN AGRICULTURAL ЕXTENSION SERVICE AND COOPERATIVES - STATE AND POSSIBILITIES - Marija; Vučković, Dejana; Mihailović, Nikola (Journal of Agricultural Sciences (Belgrade), 2023)
One of the key links in the system of knowledge and information transfer in agriculture in Serbia is extension service, which acts as mediator between scientific institutions and different groups of users. This paper aims to examine the quality of cooperation between agricultural extension service and agricultural cooperatives in Serbia, and to evaluate the views of farmers (cooperative members) on the success of this cooperation. A survey with 220 respondents, members of agricultural cooperatives, was conducted for the purpose of this research. The analysis showed that over 80% of cooperative members have cooperation with extension service, and that they are more satisfied with the quantity of extension services, than the quality. More than half of the respondents believe that it is necessary to adapt provided advices to the needs of cooperatives, and to pay more attention to cooperatives in the media appearances of extension officers. This research provides an important insight into the form and specifics of cooperation between agricultural extension service and agricultural cooperatives, on the basis of which measures can be proposed for their continuous improvement.